Analysis of de novo donor‐specific HLA‐DPB1 antibodies in kidney transplantation. (14th September 2021) - Tang, Chen; Unterrainer, Christian; Fink, Annette; Cinca, Sofia; Ruhenstroth, Andrea; Scherer, Sabine; Morath, Christian; Zeier, Martin; Mehrabi, Arianeb; Süsal, Caner; Tran, Thuong Hien
Abstract : HLA matching and avoidance of unacceptable mismatches are important aspects in the selection of donors for solid organ transplantation. The impact of HLA‐DPB1 incompatibility on the outcomes of kidney transplantation is not fully understood. We investigated a potential effect of mismatching for HLA‐DPB1 at allele, eplet, or Terasaki epitope (TerEp) level on the formation of de novo donor‐specific antibodies (dnDSA) and also asked whether polymorphisms associated with HLA‐DPB1 expression level may influence dnDSA induction. Furthermore, we analyzed the correlation between graft survival and HLA‐DPB1 mismatches defined by different approaches. A cohort of 366 patients who received a kidney transplant at the Heidelberg University Hospital, Germany, with availability of pre‐ and post‐transplant HLA antibody results by single antigen testing as well as of donor and recipient HLA‐DPB1 high‐resolution typing were analyzed retrospectively. Susceptibility to increased HLA‐DPB1 expression was predicted by the linked dimorphism rs9277534 A/G of the HLA‐DPB1 gene. Neither HLA‐DPB1 mismatches at allele, eplet or TerEp level nor exposure to donor's high HLA‐DPB1 expression were significantly associated with the risk of developing dnDSA against HLA‐DPB1. However, HLA‐DPB1 eplet and TerEp mismatches had a significant negative impact on graft survival ( p  < 0.001 and p  = 0.003, respectively). Matching for HLA‐DPB1 at epitope instead of allele level appears to have potential to improve graft survival in kidney transplantation.